2006
DOI: 10.1111/j.1460-9568.2006.04600.x
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal and parietal cortex in human episodic memory: an interference study by repetitive transcranial magnetic stimulation

Abstract: Neuroimaging findings, including repetitive transcranial magnetic stimulation (rTMS) interference, point to an engagement of prefrontal cortex (PFC) in learning and memory. Whether parietal cortex (PC) activity is causally linked to successful episodic encoding and retrieval is still uncertain. We compared the effects of event-related active or sham rTMS (a rapid-rate train coincident to the very first phases of memoranda presentation) to the left or right intraparietal sulcus, during a standardized episodic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 57 publications
7
68
1
Order By: Relevance
“…Thus, a particularly fruitful technique may be to combine functional neuroimaging and lesion approaches where patients' lesions are well-defined, and memory performance is studied in depth (Price & Friston, 2002). Another potentially useful strategy is to induce temporary functional lesions using transcranial magnetic stimulation, although the behavioral effects of this method tend to be quite small (for an initial study, see Rossi et al, 2006). Because every method in cognitive neuroscience has its own strengths and weaknesses, using a combination of them is crucial to developing a more sophisticated picture of how episodic memory is supported by the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a particularly fruitful technique may be to combine functional neuroimaging and lesion approaches where patients' lesions are well-defined, and memory performance is studied in depth (Price & Friston, 2002). Another potentially useful strategy is to induce temporary functional lesions using transcranial magnetic stimulation, although the behavioral effects of this method tend to be quite small (for an initial study, see Rossi et al, 2006). Because every method in cognitive neuroscience has its own strengths and weaknesses, using a combination of them is crucial to developing a more sophisticated picture of how episodic memory is supported by the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, most lesion studies find limited, if any, impairment in episodic retrieval (Berryhill et al 2007(Berryhill et al , 2010Haramati et al 2008), supported by an repetitive transcranial magnetic stimulation (rTMS) study that found disruption of the posterior parietal cortex does not significantly impair memory (Rossi et al 2006). A study directly comparing patients lesioned in this cortex with fMRI of healthy individuals found an anatomical overlap between the parietal recollection-related activations and the locus of the damage in patients that showed normal performance on the same task (Simons et al 2008).…”
Section: Posterior Parietal Cortexmentioning
confidence: 99%
“…4 pulses were sent for every word, with 50-ms gaps between consecutive pulses), based on previous studies which on the one hand demonstrated local interference effects following this protocol and on the other hand excluded any inter-hemispheric effect (Hamada and Ugawa 2010;Tsutsumi et al 2014;Gerloff et al 1997;Rossi et al 2002Rossi et al , 2006Rossi et al , 2011Berent et al 2015).…”
Section: Tms Protocolmentioning
confidence: 99%